Progel´s group potential of Creating creative team (2019)
The only being able to be creative is the human being, this capacity is influenced by our personality and our history, which defines some features of behaviour that can be described by the archetypes, and these features also influence how we perform as part of a team; and affects our creative abilities. The creative capacity of an organization is the combination of the creative capacity of each of its members; so, by identifying the creative abilities, archetypes and roles of each person we can describe the creative potential of an organization. The research was quantitative descriptive correlational, focusing its results on establishing the dominance in creative abilities, archetypes and team roles for each employee of the Progel Group. Taking these inputs, we analysed the information in search of correlations between team roles and archetypes; As well as between team roles and creative skills.